Theory of mind impairments in first-episode psychosis, individuals at ultra-high risk for psychosis and in first-degree relatives of schizophrenia: Systematic review and meta-analysis - Bora, Emre; Pantelis, Christos (Schizophrenia research, 2013)
Theory of mind (ToM) deficit is a well-established feature of schizophrenia and has been suggested as a vulnerability marker of this disorder. However, as most of this evidence is based on studies in chronic patients, it is less clear whether ToM is impaired prior to or following the onset of a first-episode and whether it is evident in unaffected relatives of patients. In this meta-analysis, ToM performance of 3005 individuals with first-episode psychosis (FEP), individuals at ultra-high risk for psychosis (UHR) and unaffected relatives were compared with 1351 healthy controls. ToM was substantially impaired in first-episode psychosis (Cohen d=1.0) and this deficit was comparable to findings in chronic patients. ToM was also impaired in unaffected relatives (d=0.37) and UHR subjects (d=0.45) and performances of these groups were intermediate between FES and healthy controls. Severity of ToM deficits in unaffected relatives and UHR subjects was similar to other cognitive deficits observed in these groups. Longitudinal studies of clinical and genetic high-risk subjects are necessary to investigate the trajectory of development of ToM deficits in schizophrenia.